Numerical study and parametric analysis of the propagation buckling behaviour of subsea pipe-in-pipe systems. (April 2018) - Alrsai, Mahmoud; Karampour, Hassan; Albermani, Faris
Abstract: Propagation buckling mechanisms in pipe-in-pipe (PIP) systems with thin and moderately thin carrier pipes with a diameter-to-thickness ( D o /t o ) ratio in the range 26–40 are investigated using 2D analytical and 3D nonlinear (material and geometry) finite element (FE) models. The FE models are validated against hyperbaric chamber tests of a PIP system with D o /t o of 30. Using the validated FE model a parametric study is conducted and two distinct buckle propagation modes in PIPs are observed. Empirical expressions for each mode are proposed and are found to be different from previous expressions suggested for PIPs with ( D o /t o ) ratio in the range 15–25. Highlights: Two major buckle propagation modes in PIPs are presented. Separate expressions for buckle propagation pressures of each mode are proposed. Based on the combined data from previous studies and current FE results, a more comprehensive empirical expression is suggested.